Strategies for discovery of new molecular targets for anti-infective drugs. (October 2019) - Varela, Manuel F; Kumar, Sanath
Highlights: Multidrug resistant bacterial pathogens may compromise the clinical utility of antimicrobial agents. Certain pathogenic bacteria have developed several classes of mechanisms for conferring antimicrobial resistance. Discovery of new molecular targets for novel drugs can be based on bioinformatics, metabolomics and genomics approaches. Molecular genetics and biophysical methods allow better understanding of drug-target interactions and thermodynamics. Abstract : Multidrug resistant bacterial pathogens as causative agents of infectious disease are a primary public health concern. Clinical efficacy of antimicrobial chemotherapy toward bacterial infection has been compromised in cases where causative agents are resistant to multiple structurally distinct antimicrobial agents. Modification of extant antimicrobial agents that exploit conventional bacterial targets have been developed since the advent of the antimicrobial era. This approach, while successful in certain cases, nonetheless suffers overall from the costs of development and rapid emergence of bacterial variants with confounding resistances to modified agents. Thus, additional strategies toward discovery of new molecular targets have been developed based on bioinformatics analyses and comparative genomics. These and other strategies meant to identify new molecular targets represent promising avenues for reducing emergence of bacterial infections. This short review considers these strategies for discovery of new molecular targets within bacterial pathogens.